New color photography (the). - Eauclaire, S. ([S.l.] : Meulenhoff/Landshoff, 1981)
Babis, Larry ; Bartos, Adam ; Bishop, Michael ; Callahan, Harry ; Callis, Jo Ann ; Christenberry, William ; Clay, Langdon ; Cohen, Mark ; Culver, Joyce ; Dantzic, Jerry ; Divola, John ; Eggleston, William ; Epstein, Mitch ; Faucon, Bernard ; Gowin, Emmet ; Groover, Ian ; Haxton, David ; Hess, Allen ; Hill, Douglas ; Hockney, David ; Jenshel, Len ; Karant, Barbara ; Levitt, Helen ; Maloney, Joe ; McGowan, Kenneth ; Mertin, Roger ; Meyerowitz, Joel ; Mulberg, Joanne ; Parker, Olivia ; Pfahl, John ; Ravanesi, Bill ; Rodan, Don ; Rubinfien, Leo ; Samaras, Lucas ; Schwartz, Mark ; Shore, Stephen ; Skoglund, Sandy ; Slavin, Neal ; Smith, William Eugene ; Sonneman, Eve ; Sorce, Wayne ; Steiger-Meister, Carla ; Sternfeld, Joel ; Taussig, Arthur ; Thies, Rocky ; Torbert, Stephanie ; Webb, Boyd
boek